Annual Plan 1999-2000 Volume - II Government of Manipur - Planning Commission (Planning Commission, 1999)
G.N. Statement Draft Annual Plan (1999-2000), Draft Annual Plan 1999-2000 Proposal outlay (Annexure-l) Physical Targets and Achievements Annual Plan (1999-2000) Proposals for Spill over & Ongoing Programmes/Projects as in Annexure-l (Outlay/Expenditure) and Physical Targets/Benefits in relevant units of measurements (Annexure-111-A) Draft Annual Plan 1999-2000 - Proposals for Maximising Benefits of completed programmes. Projects (Xs on 31.3.99) Draft Annual Plan 1999-2000 Proposals for Programmes/Projects - New scheme (outlay/expenditure and physical targets/benefits in relevant unit of measurements) Summary statement. Annual Plan 1999-2000 Proposal for Programmes/Projects, Statement regarding Externally Aided Projects Annual Plan 1999-2000 - Outlays By heads of Development for District Plan Centrally Sponsored Schemes.
Planning Department Government of Manipur